Diverse Responses of Multiple Satellite‐Derived Vegetation Greenup Onsets to Dry Periods in the Amazon. Issue 20 (25th October 2022) - Zhang, Xiaoyang; Shen, Yu; Gao, Shuai; Wang, Weile; Schaaf, Crystal
Abstract: Satellite‐derived vegetation greenness and seasonal dynamics in the Amazon have generated considerable academic debate over the past two decades. Despite this, the phenological timing of Amazon forests and, in particular their responses to dry periods, remain poorly understood. Here we explicitly identify the diverse timing of vegetation canopy greenup onsets from 10‐min geostationary satellite observations, and compute the timing of both the start and end of dry periods from daily precipitation data. We, for the first time, reveal that the Amazon vegetation canopy regularly experiences two cycles of greenup onsets during a year. The occurrence of greenup onset varies diversely from the start to end of the dry periods, but demonstrates regular shifts in local areas, although irregular shifts across the region. The multiple greenup onsets show complex spatial shifts, which closely follow the spatial movement of dry periods. The results provide a new insight into our understanding of the complexity of Amazonian vegetation canopy dynamics during dry periods, which could significantly improve the simulation of carbon and water cycles. Plain Language Summary: Plant greenness in the Amazon can be difficult to calculate from polar‐orbiting satellites because clouds always cover over the region continuously. However, by using geostationary satellite data collected every 10 min, and daily rainfall data, we have found that the Amazonian foliage can experience two periods of leaf greenness increase during a year, which are closely associated with multiple dry periods. The timing of greenness increase changes from the start to the end of the dry periods, in which the spatial shift can be somewhat regular in local areas, although irregular in larger regions. Our findings highlight the diverse and complex responses of tropical leaf greenness increase to dry period, which is of great significance in accurately calculating the carbon and water cycles, and their responses to climate change. Key Points: Geostationary satellites reveal that Amazon forests can experience two phenological cycles during a year Occurrence of vegetation greenup onset closely follows either the start or the end of rainy seasons across the region Greenup onset shifts regularly in local areas but irregularly across the larger region